The Effect of eWOM and Price on Brand Image and Consumer Buying Interest of Somethinc in E-Commerce - Enrikha Jihan Shalsabila Jihan; Albari (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to explain the influence of eWOM and price on brand image and purchase intention of Somethinc products in e-commerce. The research method used in this study is a quantitative approach through online questionnaire distribution, obtaining 220 respondents. The number of respondents was obtained using convenience sampling techniques based on specific criteria. The data analysis was conducted using PLS-SEM. The results of this study indicate that eWOM and price variables have a positive and significant influence on brand image, and the variables eWOM, price, and brand image also have a positive and significant influence on purchase intention. This research can contribute to the literature on purchase intention by considering the variables of eWOM, price, and brand image. For companies, the findings can be taken into consideration to strengthen relationships with consumers through e-commerce.